Non-isothermal crystallization kinetics and morphology of poly(3-hydroxybutyrate)/pluronic blends. (November 2019) - Ambrosi, Moira; Raudino, Martina; Diañez, Isabel; Martínez, Inmaculada
Graphical abstract: Different segregation degree of pluronics F68 and F127 in extralamellar domains for PHB/pluronic blends. Highlights: Poly(3-hydroxybutyrate)/pluronic blends are produced by a thermomechanical process. Crystallization process is evaluated by rheology and thermal analysis. Pluronic segregation outside the lamellar stacks promotes crystal ordering. Crystallization kinetics and blends' morphology depend on the pluronic content. Pluronic demixing extent affects blend structure and, thus, mechanical properties. Abstract: Poly(3-hydroxybutyrate), PHB, was mixed with pluronic F68 or F127 to obtain polymer blends with increased hydrophilicity and thus suitable for biomedical applications. Blend films were obtained by thermomolding keeping the pluronic content ≤17 wt% to avoid immiscibility. The non-isothermal crystallization kinetics of the blends was investigated by both differential scanning calorimetry (DSC) and rheology. PHB and pluronics were found to be miscible in the melt with both pluronics acting as diluent. Polarized optical microscopy (POM) and X-ray scattering (SAXS, WAXS) revealed that blending increased the overall crystallinity, promoting crystal ordering through the formation of more resolved, ring-banded spherulites. However, the different diffusion rate of pluronic F68 and F127 led to a different segregation extent of pluronic in the extralamellar domains with different final morphological homogeneity. The mechanical properties of the blends intimately correlated with the structure at the nano and microscale.